Foot-guided control of a biped robot through ZMP manipulation. (16th November 2020) - Yamamoto, T.; Sugihara, T.
ABSTRACT: This paper proposes a robust biped control to track the desired foot-placements, which is suitable to locomotion in complex environments. A strategy to determine the referential ZMP based only on the next pivot point and the capturability at the moment of landing improves the mobility of the robot by exploiting narrow footprints. It can run in submilliseconds since the optimal ZMP is analytically obtained from the current state of the center of mass (COM), time to land, and the desired landing position. The method does neither refer any preplanned motion trajectory nor feedback the acceleration of the COM. Thus, the robot exhibits flexible behaviors against perturbations. Although the constraint on the ZMP to be within the supporting region is not taken into account in the optimization, a post-process to saturate it by the region works in many situations. Even in severe situations where this does not work, accompanied techniques to automatically adjust the landing position and the time to land prevents the robot from falling. An enhancement of the controller based on the N -step capturability with a technique to encourage smoother manipulation of the ZMP is also proposed in order to locomote on very limited footholds. GRAPHICAL ABSTRACT: UF0001